Aporetic Interpretations of Postmodern American Dream (Journal of Asian Development Studies, 2023)
This research aims to explore and analyze the Aporetic interpretations of various versions of the American Dream in the selected plays of Edward Albee (1928-2016). Albee’s world of drama is different from that of other postmodern American playwrights. His major focus is on the various interpretations of the American dream and expounding the different issues and ideas that have changed the Postmodern American perception of American ideology. This is qualitative research as Jacques Derrida’s deconstructive term Aporia has been applied to the selected plays of Edward Albee. Various books and articles related to Aporia, the American dream, and the selected plays of Edward Albee have been discussed to explain the relationship between Derridean deconstruction, the American dream, and postmodern American drama. Edward Albee’s approach to the American stage makes the reader understand the alienation, disintegration, and disillusionment within American society. Aporia focuses on the ambiguity in the language that offers the reader a diversity of interpretations, and those interpretations can be found entirely within themselves. This research aims to explore and analyze the Aporian expression and Albee’s selected plays simultaneously.